2020
DOI: 10.2147/ijgm.s273266
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Efficacy of Baloxavir Marboxil in the Treatment of Seasonal Influenza in Adult Patients: A Prospective Observational Study</p>

Abstract: Baloxavir marboxil, a recently developed antiviral drug, has been used to treat influenza in some countries including Japan. The aim of this study was to determine the clinical efficacy of the drug, which currently remains unclear. Patients and Methods: Overall, 43 adult patients with seasonal influenza who visited the outpatient clinic of Teikyo University Hospital in Tokyo during the winter of 2018-2019 were enrolled. Of them, 14, 13, and 16 were prescribed baloxavir marboxil (40 or 80 mg once), oseltamivir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In that study, the average ± SD time to the alleviation of the fever was reported to be 1.94 ± 0.09 days for 111 patients prescribed baloxavir (a single dose oral antiviral) and 2.35 ± 0.08 days for those prescribed NAIs (oseltamivir: 74 patients, zanamivir: 24 patients, peramivir: 4 patients, and laninamivir: 77 patients), and the difference was statistically significant (p = 0.002). Shorter time to fever resolution in baloxavir (median [interquartile range]: 1.0 [1.0-2.0] days) than in laninamivir (2.0 [1.5-3.5] days, p = 0.032) was also reported in another observational study including 43 adult patients treated with baloxavir (14 patients), laninamivir (16 patients), or oseltamivir (13 patients) [28]. The median time for baloxavir was also shorter than that for oseltamivir (3.0 [1.0-3.0] days), although the difference was not statistically significant (p = 0.067).…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…In that study, the average ± SD time to the alleviation of the fever was reported to be 1.94 ± 0.09 days for 111 patients prescribed baloxavir (a single dose oral antiviral) and 2.35 ± 0.08 days for those prescribed NAIs (oseltamivir: 74 patients, zanamivir: 24 patients, peramivir: 4 patients, and laninamivir: 77 patients), and the difference was statistically significant (p = 0.002). Shorter time to fever resolution in baloxavir (median [interquartile range]: 1.0 [1.0-2.0] days) than in laninamivir (2.0 [1.5-3.5] days, p = 0.032) was also reported in another observational study including 43 adult patients treated with baloxavir (14 patients), laninamivir (16 patients), or oseltamivir (13 patients) [28]. The median time for baloxavir was also shorter than that for oseltamivir (3.0 [1.0-3.0] days), although the difference was not statistically significant (p = 0.067).…”
Section: Accepted Manuscriptsupporting
confidence: 55%
“…Baloxavir marboxil targets the cap-dependent endonuclease activity of the PA polymerase subunit of influenza viruses and prevents viral mRNA synthesis [ 44 ]. Clinical studies suggest that baloxavir treatment is more effective at reducing the duration of fever and influenza-like symptoms compared to individuals treated with NAIs [ 45 , 46 ]. However, baloxavir marboxil exhibits a low barrier of resistance, with the single PA I38T mutation leading to strains with overall fitness similar to the wild-type strain [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese post-marketing surveillance of 3,094 patients (2,198 patients aged ≥ 12 years) confirmed that BXM rapidly improved clinical symptoms and was safe regardless of age group or virus type [6]. Other Japanese studies have also found that the times to resolution of fever and the improvement of clinical symptoms were faster with BXM than with NAIs [7,8].…”
Section: Clinical Efficacy (Time To Alleviation Of Symptoms) and Anti...mentioning
confidence: 90%